English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

y = 2 - 3x
4x + 8(2 - 3x) = 1
4x + 16 - 24x = 1
- 20x = - 15
x = 3 / 4
y = 2 - 9 / 4
y = - 1 / 4
Answer is x = 3 / 4 , y = - 1 / 4

2007-07-17 19:42:09 · answer #1 · answered by Como 7 · 1 0

3x + y = 2, so y = 2 - 3x
4x + 8y = 1, so, substituting the value for y,
4x + 8(2 - 3x) = 1
4x + 16 - 24x = 1
-20x = -15
x = (-15/-20) =3/4
y = 2 - 3x = 2 - 3(3/4) = -1/4

2007-07-17 21:08:44 · answer #2 · answered by anobium625 6 · 0 0

3x+y=2...1.
x=1-8y :4...2.

so, 3(1-8y : 4)+ y =2
3-24y + 4y = 8
-20y = 5
y= - 1/4

so the answer must be A

2007-07-18 01:56:08 · answer #3 · answered by Anonymous · 0 0

a.-1/4,3/4

2007-07-18 00:06:38 · answer #4 · answered by nicky 1 · 0 0

Y?

2007-07-17 21:22:33 · answer #5 · answered by Anonymous · 0 0

fedest.com, questions and answers